Identification And Factors That Affecting The Growth Of The Indigenous Mushroom, Boletus Sp. In Bachok, Kelantan, Malaysia - Lau, Meng Fei (2014)
In Malaysia, collecting wild mushrooms for food and medicine is a well-known activity among the indigenous people (“Orang Asli”). This study was performed to identify an edible Boletus mushroom in Bachok, Kelantan based on macroscopic and microscopic characteristics of its fruiting bodies. Di Malaysia, pengumpulan cendawan liar untuk makanan dan ubatan merupakan aktiviti yang popular di kalangan “Orang Asli”. Kajian ini dijalankan untuk mengenalpasti cendawan Boletus yang boleh dimakan di Bachok, Kelantan berdasarkan ciri-ciri makroskopik dan mikroskopik jasad buahnya.